Comparison of sevoflurane and desflurane on effect-site concentration of remifentanil for preventing anesthetic emergence cough in elderly female patients undergoing laparoscopic cholecystectomy - Kim HY (Dove Medical Press, 2018)
Ha Yeon Kim,1 Yeo Rae Moon,2 Suhyun Seok,1 Bora Kim,1 Ji Eun Kim,1 Sook Young Lee1 1Department of Anesthesiology and Pain Medicine, Ajou University School of Medicine, Suwon, Republic of Korea; 2Office of Biostatistics, Ajou Research Institute for Innovation Medicine, Ajou University School of Medicine, Suwon, Republic of Korea Purpose: Among inhalational anesthetics, desflurane is widely believed to provoke upper airway irritation including coughing and laryngospasm. Remifentanil has been generally used to prevent cough due to its unique pharmacodynamics. However, there was no study that compared optimal remifentanil effect-site concentration (Ce) to prevent emergence cough according to the type of inhalational agent in elderly female patients. Thus, we investigated the Ce of remifentanil for preventing cough during emergence from sevoflurane and desflurane anesthesia in elderly female patients. Methods: Forty-three female patients between 60 and 75 years of age undergoing laparoscopic cholecystectomy were randomly allocated to sevoflurane group (n=22) or desflurane group (n=21). The optimal remifentanil Ce using target-controlled infusion for 50% of patients (EC50) and 95% of patients (EC95) was assessed by Dixon’s up-and-down method or isotonic regression method with a bootstrapping approach. Results: By Dixon’s up-and-down method, the EC50 of remifentanil in sevoflurane group (2.08±0.47 ng/mL) was comparable with that in desflurane group (2.25±0.40 ng/mL) (P=0.385). The EC50 (83% CIs) and EC95 (95% CIs) by isotonic regression also did not show significant difference between two groups [2.06 (1.45–2.23) and 2.46 (2.35–2.48) ng/mL in sevoflurane group and 2.14 (1.45–2.56) and 2.88 (2.47–2.98) ng/mL in desflurane group, respectively]. Conclusion: There was no difference in the remifentanil Ce to prevent emergence cough between sevoflurane and desflurane anesthesia. Therefore, the clinicians may not need to adjust the remifentanil Ce to prevent emergence cough according to inhalational agents in elderly female patients. Keywords: aging, cough, inhalational anesthetics, opioid, women